Sutured Intrascleral Posterior Chamber Intraocular Lens Fixation with Ciliary Sulcus Location Guided by Ultrasonic Biological Microscopy: A Retrospective Analysis of Anatomical and Refractive Outcome - Ya Qu; Ping Duan; Shujia Huo; Fuliang Li; Jiawen Li (Journal of Ophthalmology)
Purpose. To report the outcome of sutured intrascleral posterior chamber intraocular lens (PC IOL) fixation with ciliary sulcus location guided by ultrasonic biological microscopy (UBM). Methods. Patients who underwent a sutured intrascleral PC IOL fixation were reviewed and divided into four groups. In group 1, the traditional sulcus fixation (2 mm from limbus) of IOL was performed. In groups 2, 3, and 4, UBM was performed before surgery to locate the position of the ciliary sulcus as the haptics insertion position. IOL power was selected by decreasing the calculated value of the IOL power by 1.0 D, 1.0 D, 0.5 D, and 0.0 D, respectively. Results. Sixty-one patients (63 eyes) were included in the four groups. After 4.1 ± 3.0 months’ follow-up, the postsurgery spherical equivalent (SE) was 0.73 ± 1.86, 0.71 ± 0.84, 1.14 ± 0.45, and 0.07 ± 0.89 diopters (D), respectively. Statistical significance was reached for the postsurgery SE with target refraction between group 1 (p=0.027, <0.05), group 2 (p=0.003, <0.01), and group 3 (p=0.017, <0.05). No significant difference existed for the postsurgery SE with target refraction in group 4 (p=0.779, >0.05), and the postsurgery SE in group 4 was the nearest to target refraction. Conclusion. Intrascleral PC IOL fixation guided by UBM is helpful for locating the ciliary sulcus and satisfactory visual outcomes with a predictable IOL power calculation.